PENGARUH LAYANAN KONSELING KELOMPOK ISLAMI DENGAN TEKNIK REBT TERHADAP PENURUNAN FREKUENSI BERKATA KASAR PADA TEAM FUTSAL DI MTsN 3, MTsN 5 DAN MTsN 6 CIANJUR - Yunaini, Yunaini; Tajir, Hadjir; Bahrudin, Bahrudin (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
The purpose of this study was to determine the condition of Islamic Group Counseling Services using REBT techniques, the condition of swearing in the Futsal Team, and the effect of Islamic Group Counseling Services using REBT techniques on reducing the frequency of swearing in the Futsal Team at MTsN 3, MTsN 5, and MTsN 6 Cianjur. The research method used a pre-experimental method with Islamic group counseling services as the independent variable and swearing as the dependent variable. The sample used a total sampling method. Data collection techniques included observation, documentation study, and questionnaires. Instrument testing techniques included validity and reliability tests. Classical assumption tests included normality and homogeneity tests. Data analysis techniques included t-tests, correlation tests, and determination tests. This study demonstrated that Islamic group counseling services using REBT techniques were effective in reducing swearing behavior in the futsal team at MTsN 3, MTsN 5, and MTsN 6 Cianjur. There was a significant decrease in swearing behavior after the intervention, as evidenced by the T-test results (p 0.05). The service contributed 63% to this change, while other factors contributed the remaining 37%. This indicates a strong, positive correlation between counseling services and a decrease in swearing behavior.